Who's with Me? False Consensus, Brokerage, and Ethical Decision Making in Organizations - Flynn, Francis J.; Wiltermuth, Scott S. (Academy of Management Journal, 2010)
We propose that organization members overestimate the degree to which others share their views on ethical matters. Further, we argue that being a broker in an advice network exacerbates this false consensus bias. That is, a high level of “betweenness centrality” increases an individual's estimates of agreement with others on ethical issues beyond what is warranted by any actual increase in agreement. We tested these ideas in three separate samples: graduate business students, executive students, and employees. Individuals with higher betweenness centrality overestimated the level of agreement between their ethical judgments and their colleagues'.